(untitled) (Research, Society and Development, 2023)
The monitoring of child growth and development is based on anthropometric assessment in well-child care and comparison with the graphs developed by the World Health Organization, the Curves of Growth. In this way, it is possible to assess several issues, including the presence of diseases that may affect children, such as malnutrition and obesity. This research seeks to compare the Growth Curve obtained by data from the Municipality of Cascavel in children from 0 to 2 years old with the parameters determined by the Organization World Health. In general, it can be seen that this Brazilian Municipality has growth rates close to ideal when compared to the WHO Growth Curves, and that the weight and length pattern is reflected between girls and boys. However, it is also noted that males have a slightly lower percentage of findings that exceed the upper limit (Percentile 97) and the lower limit (Percentile 3) in all graphs. Therefore, it is concluded that children in the analyzed region and within the proposed age range have adequate weight and length growth, especially among females.